Avaliação do potencial da macrófita Pistia stratiotes na exposição de íon cromo (VI): biossorção e tolerância - Moresco, Camila (2016)
The environmental pollution caused by industries has increased the concentration of pollutants in the environment, especially in water. Among the most diverse contaminants, there is the metals, who may or may not to be heavy/toxic, causing effluent of difficult treatment when in low concentrations. The search for alternative measures of wastewater effluent treatment has led to studies using phytoremediation technique through the various matrices (plant, fungi, bacteria) as means of polishing treatment to remove contaminants by means of biosorption/bioaccumulation. In order to use the phytoremediation technique for removing metals of the environmental, it have been performed bioassay with the macrophyte Pistia stratiotes. The bioassays were realized with healthy plants of P. stratiotes acclimatized in a greenhouse, at room temperature and lighting conditions during 28 days of cultivate. The cultivations were performed in glass vessels containing 1 L of the hydroponic solution with chromium (VI) in the potassium dichromate form with concentration range 0.10 to 4.90 mg L-1. The experiments were performed by Outlining Central Composite Rotational (OCCR), where the kinetics of bioaccumulation and chlorophyll a fluorescence were monitored in plants of P. stratiotes during cultivation. The collections of the samples and cultive solution were performed according to the OCCR. The chromium levels were measured in samples of P. stratiotes and the remaining solutions by the methodology of atomic absorption spectrometry by flame. The tolerance of P. stratiotes in relation to exposure to chromium (VI) was analyzed by parameters of physiological activity by means of chlorophyll a fluorescence, using the portable fluorometer PAM (Pulse Amplitude Modulation). The development of P. stratiots and their biomass were related to the time factor, while bioaccumulation capacities were strongly influenced by factors of time and chromium concentration (VI). The chlorophyll fluorescence parameters were affected by chromium and the exposure time at the bioassays. It was obtained an higher metal removal from the root in relation to the sheet, reaching a high rate of metal removal in solution. The experimental data removal kinetics were represented by kinetic models Irreversibly Langmuir, Reversible Langmuir, Pseudo-first Order and Pseudo-second Order, and the best fit for the culture solution was the Reversible Langmuir model with R² 0.993 and for the plant the best model was Pseudo-second order with R² 0.760.